Enantioselective desymmetrisation of an epoxytropinone for peduncularine synthesis - Shelton, RE; Sezer, S; Hodgson, DM (Elsevier, 2020)
A key 7-allyl-8-hydroxy-6-azabicyclo[3.2.1]octan-3-one intermediate in a synthesis of the alkaloid peduncularine is obtained enantioenriched, by desymmetrisation of an achiral 6,7-epoxy-8-azabicyclo[3.2.1]octan-3-one (epoxytropinone). Chiral lithium amide-assisted enantioselective silyl enol ether formation then TMSOTf/allyltrimethylsilane/2,6-lutidine-induced rearrangement−allylation proceeded in up to 80:20 er, but modest overall yield. Chiral amines or (thio)ureas replacing 2,6-lutidine gave up to 76:24 er directly from epoxytropinone. A direct, simplified (base-free) process using a BINOL-derived bis(sulfuryl)imide catalyst and allyltrimethylsilane proved the most promising (80%, 83:17 er).